INOVASI DESAIN VISUAL DAN BRANDING PRODUK COSPLAY: STUDI POTENSIAL DALAM PROYEK PERANCANGAN TEKNIK DAN SISTEM INDUSTRI - Chandra, Edy (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
The creative industry is rapidly evolving, presenting product innovations that originate from visual ideas, one of which is cosplay product design. Currently, cosplay has become a major trend among Generation Z in Indonesia, as reflected in the dynamic growth of cosplay communities and events that stimulate the demand for creative products with strong visual identities. This study aims to analyze the potential for innovation in visual design and branding of cosplay products as a prospective study in engineering and industrial system design projects. A case study is conducted on the development of themed textile products by Cosplay Fabrics by Wyla, which translates creative visual concepts into industrial materials specifically designed for the cosplay community. The research method employs market needs analysis, visual design studies, and identification of branding strategies. The results show that cosplay products developed professionally with strong visual branding can enhance competitiveness, added value, and user loyalty. This study concludes that creative product objects such as cosplay hold significant potential to be adopted in engineering and industrial system design projects as a form of visual design-based innovation that is highly relevant to modern industrial development.